THE EFFECT OF TASK REPETITION ON ORAL FLUENCY AND ACCURACY IN SECOND-YEAR STUDENTS AT UFLS, UDN - Thuan , Phung Tan; Anh , Vo Thi Quynh (INTERNATIONAL JOURNAL OF HUMANITIES, PHILOSOPHY AND LANGUAGES (IJHPL), 2025)
This study investigates the effect of task repetition on oral fluency and accuracy in second-year students at the Faculty of English, University of Foreign Language Studies (UFLS), the University of Danang. Recognizing that developing oral fluency and accuracy in speaking remains a challenge for L2 learners, particularly second-year students, this research aimed to determine if repeating oral tasks would lead to significant improvements in these areas. A control experiment was conducted with a sample of 24 second-year students who engaged in a series of oral tasks designed to assess both fluency and accuracy. The study compared a task repetition (TR) group with a control group. Oral fluency was measured as speech rate (meaningful syllables per minute), and oral accuracy was measured as the percentage of error-free clauses. The analysis of the data revealed a statistically significant positive effect of task repetition on the accuracy of the TR group in the second trial of the task. It also suggested that learners in TR group had greater accuracy compared to ones in control group. These results indicate that repeating the task facilitated a reduction in errors and an increase in the production of error-free clauses. However, the study did not find a statistically significant effect of task repetition on speech rate. The study concludes that task repetition can enhance accuracy in monologic speaking tasks, but its influence on fluency, as measured by speech rate, was not statistically supported in this context.